Application of Whatsapp In Learning in The Subject Of The Human Reproductive System Of IX E Class SMP Negeri 1 Latambaga Year 2019 - Didiet Ekzar (Amanah: Jurnal Amanah Pendidikan dan Pengajaran, 2020)
The purpose of this study was to determine the use of the Whatsapp application in learning on the subject of the human reproductive system in class IXE at SMP Negeri 1 Latambaga for the 2018/2019 academic year. This research was conducted through several processes, namely: (1) planning, (2) action, (3) observation or observation, and (4) reflection on the four steps that constitute one cycle. For data management the results of the study were carried out by tabulating the value of each student from several aspects of the assessment that had been predetermined by the researcher which was composed as a research instrument. From the data analysis, it was found that in Cycle I which caused students classically to have not reached the Minimum Learning Completion Criteria (KBM) because it was influenced by several factors, including the ability to understand the material which was still quite low for students and in Cycle II the results showed that The minimum learning completeness criteria have been achieved well so that there is an increase in student learning outcomes in using the Whatsapp application in Class IXE at SMP Negeri 1 Latambaga